Pengaruh Influencer Marketing dan Brand Image terhadap Minat Beli Konsumen Kaymara.id - Faturrahman Panji Perman; Dede R. Oktini; Septiana Ayu Mahani (UNISBA Press, 2024)
Abtract: This research is related to how product quality, service quality and store atmosphere influence customer satisfaction at Katsuin. The aim of this research is to find out how product quality, service quality and store atmosphere influence customer satisfaction at Katsuin, both partially and simultaneously. The method used is a quantitative method, with data collection techniques using questionnaires. The subjects or samples used in this research were 241 respondents. The sampling technique is purposive sampling. Data processing in this research uses SPSS version 26. The results of this research show that Product Quality has a partial and significant influence on Customer Satisfaction with a t test of 0.000, while Service Quality has a partial and significant influence on Customer Satisfaction with a t test of 0.008, then Store Atmosphere has a partial and significant influence on Satisfaction Customers with a t test value of 0.000. And Product Quality, Service Quality and Store Atmosphere on Customer Satisfaction have a simultaneous and significant influence with an f test value of 0.000. It is hoped that future researchers will research issues that can have an influence on customer satisfaction in addition to the variables already studied. Abstrak. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana gambaran influencer marketing dan brand image terhadap minat beli pada kaymara.id. Serta untuk mengetahui pengaruh influencer marketing, brand image terhadap minat beli. Penelitian ini menggunakan metode penelitian kuantitatif dan termasuk dalam kategori penelitian deskriptif dan verifikatif. Penelitian ini menggunakan metode nonprobability sampling yaitu purposive sampling untuk mengumpulkan data dari 100 orang mahasiswa di Kota Bandung sebagai responden penelitian minat beli. Analisis deskriptif dan verifikatif menggunakan regresi linier berganda, uji f, uji t, dan koefisien determinasi digunakan dalam penelitian ini. Temuan penelitian ini menunjukkan bahwa influencer marketing dan brand image mempunyai pengaruh terhadap minat beli konsumen. Selanjutnya, baik influencer marketing maupun brand image secara simultan berpengaruh terhadap keputusan pembelian.